Effect of magnetic fields on cryptochrome-dependent responses in Arabidopsis thaliana - Harris, S; Henbest, K; Maeda, K; Pannell, J; Timmel, C; Hore, P; Okamoto, H (Royal Society Publishing, 2009)
The scientific literature describing the effects of weak magnetic fields on living systems contains a plethora of contradictory reports, few successful independent replication studies and a dearth of plausible biophysical interaction mechanisms. Most such investigations have been unsystematic, devoid of testable theoretical predictions and, ultimately, unconvincing. A recent study, of magnetic responses in the model plant Arabidopsis thaliana, however, stands out; it has a clear hypothesis - that seedling growth is magnetically sensitive as a result of photoinduced radical-pair reactions in cryptochrome photoreceptors - tested by measuring several cryptochrome-dependent responses, all of which proved to be enhanced in a magnetic field of intensity 500 μT. The potential importance of this study in the debate on putative effects of extremely low-frequency electromagnetic fields on human health prompted us to subject it to the 'gold standard' of independent replication. With experimental conditions chosen to match those of the original study, we have measured hypocotyl lengths and anthocyanin accumulation for Arabidopsis seedlings grown in a 500 μT magnetic field, with simultaneous control experiments at 50 μT, 1 mT and approximately 100 mT magnetic fields (with zero-field controls), measured gene (CHS, HY5 and GST) expression levels, investigated blue-light intensity effects and explored the influence of sucrose in the growth medium. In no case were consistent, statistically significant magnetic field responses detected.